Band-Gap Engineering of NaNbO3 for Photocatalytic H2 Evolution with Visible Light - Peng Li; Hideki Abe; Jinhua Ye (International Journal of Photoenergy)
A new visible light response photocatalyst has been developed for H2 evolution from methanol solution by elemental doping. With lanthanum and cobalt dopants, the photoabsorption edge of NaNbO3 was effectively shifted to the visible light region. It is also found that the photoabsorption edge is effectively controlled by the dopant concentration. Under visible light irradiation, H2 was successfully generated over the doped NaNbO3 samples and a rate of 12 μmol·h−1 was achieved over (LaCo)0.03(NaNb)0.97O3. Densityfunctional theory calculations show that Co-induced impurity states are formed in the band gap of NaNbO3 and this is considered to be the origin of visible-light absorption upon doping with La and Co.